NURSERY OF CANTIK GROUPER (Epinephelus fuscoguttatus × Epinephelus microdon) BASED RECIRCULATION AND BIOREMEDIATION FOR AQUABUSINESS EFFICIENCY (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
Nursery of cantik grouper is generally carried out with regular water changes every day so that it is susceptible to decreased water quality and production performance. Grouper nursery with recirculation and bioremediation systems is expected to improve production performance by improving water quality. This study aims to analyze grouper nursery based on RAS (Recirculating aquaculture system) and bioremediation to improve aquabusiness efficiency. This study was conducted for 40 days using a completely randomized design with three treatments and four replications. The study used three treatment systems, namely conventional systems without recirculation and without bioremediation (SK), recirculation systems without bioremediation (RAS), and recirculation and bioremediation systems (RB). The fish used in the research were grouper seeds with an average initial length of 3.6±0.2 cm with a stocking density of 500 fish/m3. The results showed that the best survival rate and absolute length growth rate were obtained in the recirculation system with bioremeciation of 94.8±0.37%, and 0.1098±0.0029 cm/day. Grouper nursery business with recirculation and bioremediation systems was able to increase profits by 41.76% and 8.81% more efficiently than the routine water change system.